2016
DOI: 10.1038/srep37284
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic Epidemiology of Glucose-6-Phosphate Dehydrogenase Deficiency in the Arab World

Abstract: A systematic search was implemented using four literature databases (PubMed, Embase, Science Direct and Web of Science) to capture all the causative mutations of Glucose-6-phosphate dehydrogenase (G6PD) deficiency (G6PDD) in the 22 Arab countries. Our search yielded 43 studies that captured 33 mutations (23 missense, one silent, two deletions, and seven intronic mutations), in 3,430 Arab patients with G6PDD. The 23 missense mutations were then subjected to phenotypic classification using in silico prediction t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
45
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 44 publications
1
45
0
Order By: Relevance
“…B). The loss of hydrophobic and negatively charged interaction might lead to loss of thermodynamics stability [George et al, ; Doss et al, ]. This supports that the loss of hydrophobic residue (VAL90) and negatively charged residue (ASP91) might serve the reason for destabilization of protein due to G1691S.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…B). The loss of hydrophobic and negatively charged interaction might lead to loss of thermodynamics stability [George et al, ; Doss et al, ]. This supports that the loss of hydrophobic residue (VAL90) and negatively charged residue (ASP91) might serve the reason for destabilization of protein due to G1691S.…”
Section: Discussionmentioning
confidence: 87%
“…The number of variants responsible for genetic disorders are being deposited in public databases is increasing rapidly. Recent technological advances and cost‐effectiveness in genomic analysis have largely involved in understanding the relationship between the disease and missense variants [Doss et al, ]. The distinction between the variants which affect the protein structure and function from those who have little or no effect from larger pool of data obtained through experimental techniques is highly tedious [Doss et al, ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our subgroup and meta-regression analysis did not indicate any significant difference by period, region, or sample size; however, heterogeneity was still observed within subgroups. Consanguinity is part of the endogenous Arab culture, with a significant high prevalence of first-cousin marriage [29], which is still rising in some Arab countries [30], which is found to be responsible for the high prevalence of genetic diseases in the Arab countries [8,9,[31][32][33]. Few studies (n = 5) reported the consanguinity [21,26,27,30,34] (Table 1).…”
Section: Discussionmentioning
confidence: 99%